The Impact Of Small Businesses On The Implementation Of Public Procurement In Uzbekistan - Ismoilov, Botir Mukhamedovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the role, influence and level of participation of small businesses in the process of implementing public procurement in the Republic of Uzbekistan. The study used official statistics and open source data for 2024–2025. The article covers reforms aimed at increasing the activity of small businesses in the economy through public procurement, supporting local producers, as well as digitizing tender processes and ensuring transparency. It also presents factors that hinder the participation of small businesses in public procurement and offers suggestions for their elimination. The results of the study provide important practical conclusions for strengthening the role of small businesses in the economy of Uzbekistan.